The bacterial effector HopZ1a acetylates MKK7 to suppress plant immunity. Issue 3 (5th June 2021) - Rufián, José S.; Rueda‐Blanco, Javier; López‐Márquez, Diego; Macho, Alberto P.; Beuzón, Carmen R.; Ruiz‐Albert, Javier
Summary: The Pseudomonas syringae type III secretion system translocates effector proteins into the host cell cytosol to suppress plant basal immunity. Effector HopZ1a suppresses local and systemic immunity triggered by pathogen‐associated molecular patterns (PAMPs) and effectors, through target acetylation. HopZ1a has been shown to target several plant proteins, but none fully substantiates HopZ1a‐associated immune suppression. Here, we investigate Arabidopsis thaliana mitogen‐activated protein kinase kinases (MKKs) as potential targets, focusing on AtMKK7, a positive regulator of local and systemic immunity. We analyse HopZ1a interference with AtMKK7 by translocation of HopZ1a from bacteria inoculated into Arabidopsis expressing MKK7 from an inducible promoter. Reciprocal phenotypes are analysed on plants expressing a construct quenching MKK7 native expression. We analyse HopZ1a–MKK7 interaction by three independent methods, and the relevance of acetylation by in vitro kinase and in planta functional assays. We demonstrate the AtMKK7 contribution to immune signalling showing MKK7‐dependent flg22‐induced reactive oxygen species (ROS) burst, MAP kinas (MAPK) activation and callose deposition, plus AvrRpt2‐triggered MKK7‐dependent signalling. Furthermore, we demonstrate HopZ1a suppression of all MKK7‐dependent responses, HopZ1a–MKK7 interaction in planta and HopZ1a acetylation of MKK7 with a lysine required for full kinase activity. We demonstrate that HopZ1a targets AtMKK7 to suppress local and systemic plant immunity.